Greenhouses with profitable farming - del Carpio Salinas, Jorge Alberto (2005)
Designing and building a system of hidropónico cultivation was the purpose of this work to evaluate the system of control of temperature, humidity, watering and brightness in a hothouse of 50m2. There were cultivated tomatoes and lettuces, integrates to a cultivation of mushrooms eatable “mushrooms” during the months of December to February. The hidropónico cultivations were fed through watering by leak of nutritious solutions controlled with a team electronic prototype. The cultivation of “mushrooms” was fed with compost and watered through by leak. Both cultivations were watered the one of the other one independently according to the plan of programmed watering. The high temperatures registered to the interior of the hothouses during the day affected the appropriate growth and productivity of the cultivations; they also overflowed the team of environment control. Designing and building was made to a meteorological station that was available at the end of the project it was better version than the first prototype. All the teams were connected in a net RS845 that was configured to send digital values to a personal computer with user’s interface to store and to administer a database in MYSQL.